The Role of Islamic Religious Education Curriculum in Shaping Students' Morals and Ethics at Junior High School - Aimah, Siti (AFKARINA: Jurnal Pendidikan Agama Islam, 2023)
This study aims to evaluate the role of the Islamic Religious Education (PAI) curriculum in shaping students' morals and ethics in Junior High Schools (SMP). The background of this study focuses on the importance of integrating religious values in education for the development of students' character amidst the challenges of globalization and social change. The research method used is a qualitative approach with in-depth interview techniques and curriculum document analysis. The results of the study indicate that the PAI curriculum significantly contributes to the formation of students' morals and ethics, with the integration of moral values in each PAI subject strengthening positive behavior and building students' character. The main contribution of this finding is to provide a basis for the development of a more effective PAI curriculum in facilitating the development of students' character and offering guidance for policy makers and educators in improving the quality of religious education in schools.